(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
The purposes of this study were to determine how effective the Inquiry Method implementation in increasing the students’ grammatical competence, and to find out the students’ responses in applying Inquiry Method in increasing their grammatical competence at the eleventh grade of social science students in SMAN 21 Makassar in the Academic Year of 2022/2023. The result showed that increasing grammar competence by using Inquiry method was effective. Where the score of post-test was higher than pre-test which was proven by 2690 and 1825. The average for the post-test was 89.6 and 60.83 for the pre-test. After using this method, the students agreed that inquiry method have advantages in learning English, and they also agreed that inquiry method could improve their grammar competence.